THE DIFFICULTIES AND PROBLEMS FACED BY INDONESIAN STUDENTS WHILE STUDYING IN AN AUSTRALIAN UNIVERSITY - Saiful (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2013)
One of the issues that relates to Indonesian international students’ perceptions about the quality of higher education is with regards to the difficulties and problems they face while studying in an Australian university. A survey was conducted with 78 First Year to Fourth Year Indonesian international undergraduate students undergoing a range of programs and courses at a university in Australia to determine their perspective of quality in higher education. Further interviews were carried out with nine Indonesian international students to gain insights into their difficulties and learning experiences. Based on these interviews, the three main difficulties highlighted by Indonesianinternational students are: different learning styles, cultural barriers and language problems. This paper seeks to highlight the initial problems faced by Indonesian international students in terms of learning styles and how they strive to overcome these difficulties through discussions and practice. These findings present implications for the use of appropriate teaching strategies with Indonesian international students.